(untitled) (European Journal of Marketing and Economics, 2024)
This study examines how networking and institutional support mechanisms influence the international performance and competitiveness of Bulgarian enterprises, with a particular focus on small and medium-sized enterprises (SMEs). Drawing on data from a nationally representative survey, the analysis accounts for firm-level differences in size, sector, location, ownership structure (family vs. non-family), and entrepreneur characteristics such as age and gender. The research investigates how participation in business networks contributes to access to public support services, knowledge exchange, and strategic partnerships that facilitate internationalization. It also explores the extent to which personal attributes of entrepreneurs correlate with both network engagement and the likelihood of seeking institutional support. Findings suggest that active involvement in formal and informal networks, coupled with targeted institutional backing, significantly enhances the international competitiveness of SMEs. Based on these results, the paper proposes actionable policy and managerial recommendations to improve the internationalization readiness of Bulgarian enterprises. These insights contribute to the broader understanding of how non-market mechanisms and institutional infrastructure can shape economic performance in emerging markets.